Punica granatum peel supplementation attenuates cognitive deficits and brain injury in rat by targeting the Nrf2‐HO‐1 pathway. Issue 1 (12th September 2022) - Akbarian, Mahsan; Hosseini, Mahmoud; Mirzavi, Farshad; Amirahmadi, Sabiheh; Arab, Fahimeh Lavi; Rajabian, Arezoo
Abstract: The critical role of nutrition to prevent neurodegenerative disorders is well documented. Punica granatum fruit is identified as a highly nutritional food for alleviating various ailments. The ameliorating properties of P. granatum peel on memory dysfunction and the possible roles of oxidative stress, acetylcholinesterase (AchE), and nuclear factor erythroid 2‐related factor 2 (Nrf2)‐heme oxygenase (HO)‐1 pathway in the scopolamine‐treated rats were assessed. The hydroethanolic extract was standardized using high‐performance liquid chromatography (HPLC). The animal groups were as follows: Control, scopolamine (2 mg/kg), and treatment groups (the extract at doses of 200–800 mg/kg). The behavioral performance was evaluated using the Morris water maze (MWM) and passive avoidance equipment. Various biochemical parameters were then measured. Rats received the extract properly found on the platform location, indicated by a shorter traveling time and distance during 5 days of learning MWM. Moreover, the extract increased the delay and light time, while decreasing dark time and the frequency of entries to the dark in the passive avoidance test. The extract also exerted a significant increase in superoxide dismutase activity and thiol content, while decreasing AchE activity and lipid peroxidation in the brain of scopolamine‐injured rats. Our results demonstrated the neuroprotective effects of P. granatum peel in minimizing scopolamine injury possibly through targeting the Nrf2‐HO‐1 pathway. Abstract : The hydro‐ethanolic extract of P. granatum peel was standardized. ;The extract increased superoxide dismutase activity and thiol content, while reduced function of AchE and peroxidation of lipid in the scopolamine‐injured rat's brain. ;P. granatum may attenuate scopolamine injury through targeting nuclear factor‐E2‐related factor 2 pathway ;